(untitled) (Clinics, 2015)
OBJECTIVE: This study sought to describe and analyze ocular findings associated with nonocular surgery in patients who underwent general anesthesia. METHODS: The authors retrospectively collected a series of 39,431 surgeries using standardized data forms. RESULTS: Ocular findings were reported in 9 cases (2.3:10,000), which involved patients with a mean age of 58.9±19.5 years. These cases involved patients classified as ASA I (33%), ASA II (55%) or ASA III (11%). General anesthesia with propofol and remifentanil was used in 4 cases, balanced general anesthesia was used in 4 cases, and regional block was used in combination with balanced general anesthesia in one case. Five patients (55%) underwent surgery in the supine position, one patient (11%) underwent surgery in the lithotomy position, two patients (22%) underwent surgery in the prone position, and one patient (11%) underwent surgery in the lateral position. Ocular hyperemia was detected in most (77%) of the 9 cases with ocular findings; pain/burning of the eyes, visual impairment, eye discharge and photophobia were observed in 55%, 11%, 11% and 11%, respectively, of these 9 cases. No cases involved permanent ocular injury or vision loss. CONCLUSION: Ophthalmological findings after surgeries were uncommon, and most of the included patients were relatively healthy. Minor complications, such as dehydration or superficial ocular trauma, should be prevented by following systematic protocols that provide appropriate ocular occlusion with a lubricating ointment and protect the eye with an acrylic occluder. These procedures will refine the quality of anesthesia services and avoid discomfort among patients, surgeons and anesthesia staff.